THE IMPLEMENTATION OF PROJECT-BASED LEARNING (PBL): VIDEO PRODUCTION AS A PROJECT IN TEACHING SPEAKING SKILL - Iman Hilmansyah (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2022)
The research is aimed to answer the question how project-based learning using video production is implemented in speaking class. The research also tries to find out whether or not the implementation of project-based learning using video production in speaking class significantly improves students’ speaking skill. Furthermore, the students’ responses to the implementation of project-based learning using video production are also investigated. This research involved two classes. The data were analyzed by using mixed method. The results showed that all of the activities in the classroom met the standard of PBL classroom activities. However, in the learning process, the students found the problems in how to construct the sentence, pronounce the word, and record and edit the video. The teacher become the facilitator to solve their problems. Overall, the students learn how to speak while creating the project. The result of the statistical computation showed that the implementation of project-based learning using video production improved students’ speaking skill by the value of tobt(9.811) which greater than tcrit (2.002, ?=0.05, df= 58). In conclusion, the null hypothesis was rejected. In addition, the data from questionnaire demonstrated that the students show positive response toward the implementation of project-based learning using video production.